A solid oxide fuel cell anode material and its preparation method and application

The composite anode material with a heterogeneous interface with a multiphase through self-assembly and in-situ reconstruction method was prepared, which solved the problem of insufficient carbon deposit resistance and low catalytic activity in the hydrocarbon fuel atmosphere, and achieved efficient fuel electrochemical oxidation reaction and excellent durability.

CN118693293BActive Publication Date: 2025-03-11SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410853922.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-03-11
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The existing solid oxide fuel cell (SOFC) anode materials have problems such as insufficient carbon deposit resistance and low catalytic activity in hydrocarbon fuel atmosphere, resulting in insufficient durability and efficiency during long-term operation.

Method used

The self-assembly-in-situ reconstruction method is used to prepare a composite anode material with a heterogeneous interface with a multiphase heterogeneous interface by the sol-gel method. The specific steps include reducing and reconstructing (La1-xCex)(Ni1-2yCoyFey)O3-δ and Ce0.8Sm0.2O1.9 as precursors under a mixed atmosphere of hydrogen and argon to form a structure in which the multiphase nanoparticles of active metal and metal oxide are uniformly distributed.

Benefits of technology

The catalytic activity and carbon deposit resistance of the anode material are significantly improved, the ion/electron conduction path is optimized, the transmission and diffusion and electrochemical reaction capabilities of fuel gas are enhanced, and the overall performance of SOFC is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118693293B_ABST
    Figure CN118693293B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solid oxide fuel cells, and specifically relates to a solid oxide fuel cell anode material and a preparation method and application thereof, with a self-assembled (La 1‑x Ce x )(Ni 1‑2y Co y Fe y ) 3‑δ ‑Ce 0.8 Sm 0.2 O 1.9 The anode material of the present invention has mild preparation conditions, simple and efficient process, high controllability, and easy repeatability, and has broad application prospects in the preparation of high-performance electrode materials for fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid oxide fuel cells, and in particular relates to a method for preparing anode materials for solid oxide fuel cells. Background Art

[0002] Solid oxide fuel cells (SOFCs) can directly convert chemical energy in fuels into electrical energy, and have many advantages such as high energy conversion efficiency and environmental friendliness. However, due to the serious carbon deposition problem, one of the most commonly used anodes in commercial applications, nickel-yttrium stabilized zirconia (Ni-YSZ) cermet, has been proven to be no longer suitable as a direct hydrocarbon SOFC anode. Ni has excellent catalytic activity for hydrogen oxidation reactions and C-H bond cleavage. However, Ni is a very active catalyst for carbon deposition reactions. Catalytic deactivation caused by carbon deposition inhibits the direct utilization of hydrocarbons in SOFCs. In addition, at high temperatures, Ni is easily agglomerated in hydrocarbon atmospheres, which may lead to insufficient durability for long-term operation and make Ni-based cermet anodes unsuitable for commercial direct hydrocarbon fuel SOFCs.

[0003] In fact, it is challenging to develop a single-phase material that meets all the requirements of hydrocarbon-fueled SOFC anodes. Instead, the rational design of composite electrodes, in which each component serves its specific function, may be a more promising approach. For example, combining perovskite oxides with oxygen ion conductors (e.g., doped CeO2) not only promotes oxygen ion transfer but also stabilizes the anode / electrolyte interfacial contact, ultimately leading to a significant reduction in polarization resistance. Constructing metal-oxide heterointerfaces is another feasible approach to promote the intrinsic activity of electrocatalysts. For example, Tan et al. (ACS Nano, 17 (2023) 13985-13996) reported that Pr 0.8 Sr 1.2 Ni 0.2 Fe 1.3 Mo 0.5 O 6-δ (PSNFM) anodes for direct utilization of propane. For example, Yang et al. (Nature communications, 2 (2011) 357) developed a novel BaO / Ni nanointerface in a commercial Ni-YSZ anode and achieved a peak power density of ∼0.88 W cm-2 at 750 °C using dry C3H8 as fuel. -2 More importantly, the single cell can be used at 750℃C3H8 at 0.5A cm -2The constant current density discharge for 100 h indicated that the anode had excellent carbon removal ability. The nanoscale BaO on the surface of Ni grains created abundant BaO / Ni nanointerfaces with effective water absorption. The presence of water could promote the carbon removal reaction in the anode. The results showed that nanoscale metal / oxide catalysts could be used to improve the anti-carbon deposition ability of anodes. In particular, in situ exsolution has become an advanced strategy to precisely manipulate metal-oxide heterointerfaces. Most importantly, the exsoluted heterointerfaces have unique advantages, including metal oxide heterointerfaces for synergistic electrocatalysis, strong metal-oxide interactions for reducing carbon deposition and metal nanoparticle agglomeration, and reversible structures during redox cycling. Therefore, introducing oxygen ion conductors and constructing metal oxide heterointerfaces are effective solutions to improve the performance of perovskite anodes. However, developing a preparation method for heteroanodes with precisely regulated composition and morphology to achieve both high characteristic activity and fast oxygen ion conduction is a major challenge.

[0004] However, the contact between the phases of the composite anode prepared by the conventional mechanical mixing method is at the micron level, which limits the TPB area, and the surface modification method is too complicated and the multiphase distribution is uneven. In order to obtain a composite electrode material with nanoscale contact, Shao et al. (Advanced Materials, 2020, 32(8), 1906979) used a self-assembly method to develop a Co-free cathode material Sr 0.9 Ce 0.1 Fe 0.8 Ni 0.2 O 3-δ The material consists of a single perovskite phase (SrFeO 3-δ ), a RP phase (Sr4Fe3O 10-δ ) and a small amount of surface-modified NiO and CeO2. The presence of the RP phase promotes the oxygen bulk diffusion capacity of the material, and the surface-modified NiO and CeO2 enhance the oxygen adsorption and dissociation capacity of the material. In addition, the material has excellent ORR catalytic activity. The single cell assembled with SDC as the electrolyte can achieve a maximum power density of 1.21 W cm at 650 °C. -2 Hou et al. (Journal of Power Sources, 2020, 466, 228240) also used the self-assembly method to design and develop La 0.5 Sr 1.5 MnO 4+δ -La 0.5 Sr 0.5 MnO 3-δ The self-assembled cathode material was found to have good catalytic activity at a contact scale of 20-40 nm between the two phases. p Only 0.082Ωcm2 .

[0005] In view of this, it is urgent to develop a SOFC perovskite anode material with high catalytic activity and strong stability by regulating the anode morphology and structure and the distribution characteristics of active metal sites. It is of great significance not only to improve the anode's ability to resist carbon deposition in hydrocarbon fuel atmospheres, but also to significantly enhance the catalytic activity of fuel electrochemical oxidation. We proposed a new strategy that can be used for self-assembly-in situ reconstruction of hybrid material interfaces, which greatly improved the chemical composition and morphology of the composite material, and may create new breakthrough opportunities in the field of composite catalyst preparation in the future. Summary of the invention

[0006] The present invention mainly provides a solid oxide fuel cell anode material with multiphase heterogeneous interface composite, and a simple, easy and low-cost sol-gel method combined with a self-assembly-in-situ reconstruction preparation method to solve the problems of poor stability and insufficient catalytic activity of existing solid oxide fuel cells:

[0007] A solid oxide fuel cell anode material, based on self-assembled (La 1-x Ce x )(Ni 1-2y Co y Fe y ) 3-δ -Ce 0.8 Sm 0.2 O 1.9 is a precursor, which is reduced and reconstructed in situ, wherein the value range of x is 0≤x≤0.3, the value range of y is 0≤y≤0.2, δ is the oxygen vacancy content, 0≤δ≤0.15; the (La 1-x Ce x )(Ni 1-2y Co y Fe y ) 3-δ The mass percentage is 50-70%, Ce 0.8 Sm 0.2 O 1.9 The mass percentage is 30-50%.

[0008] Further, it is prepared from lanthanum, cerium, nickel, cobalt, iron and samarium ions with the molar ratio of x or y elements.

[0009] Furthermore, the anode material is a structure in which active metal and metal oxide multiphase nanoparticles are evenly distributed; when y is not equal to 0, the active metal nanoparticles are NiCoFe alloy.

[0010] A method for preparing the above-mentioned solid oxide fuel cell anode material comprises the following steps:

[0011] (1) nitrates of lanthanum, cerium, nickel, cobalt and iron are mixed and dissolved in water, and then ammonia water in which ethylenediaminetetraacetic acid is dissolved is added and mixed uniformly to obtain a metal ion solution A;

[0012] (2) samarium and cerium nitrates are mixed and dissolved in water, and then ammonia water in which ethylenediaminetetraacetic acid is dissolved is added and mixed evenly to obtain a metal ion solution B;

[0013] (3) adding citric acid to metal ion solution A and metal ion solution B respectively, adjusting the pH of the solution with aqueous ammonia, and stirring the mixture at 80-90° C. to obtain sol A and sol B respectively;

[0014] (4) mixing sol A and sol B and continuing to stir to obtain a precursor gel;

[0015] (5) drying the precursor gel at 100-120° C. for 12-18 h, and then calcining at 750-800° C. for 5-10 h to obtain a precursor;

[0016] (6) The obtained precursor is reduced in a mixed gas atmosphere of hydrogen and argon at a hydrogen flow rate of 70 to 90 mL / min to obtain an anode material.

[0017] Furthermore, the molar ratio of ethylenediaminetetraacetic acid to metal ions in metal ion solution A and metal ion solution B in step (1) and step (2) is 1:1; and the total concentration of metal ions in metal ion solution A and metal ion solution B in step (1) and step (2) is 0.15 to 0.33 mol / L.

[0018] Furthermore, in step (3), the pH value of the solution is adjusted to 6-7; in step (3), the molar ratio of citric acid to the metal ions in the metal ion solution A and the metal ion solution B is 1:(1.5-2).

[0019] Furthermore, the stirring time in step (4) is 4 to 6 hours.

[0020] Furthermore, after the calcination in step (5), the slurry is sieved through a 200-300 mesh sieve.

[0021] Furthermore, the volume of hydrogen in step (6) accounts for 5-10% of the mixed gas; the reduction temperature is 650-750° C., and the time is 2-3 hours.

[0022] An application of the above-mentioned solid oxide fuel cell anode material in a carbon deposition resistant solid oxide fuel cell.

[0023] By adopting the above scheme, the method of the present invention has the following advantages:

[0024] 1. The present invention utilizes a low-cost self-assembly-in-situ reconstruction method to obtain precursor powder, and through a simple and easy reduction and reconstruction pathway, the perovskite oxide is in-situ deconstructed to form small-sized uniformly distributed multiphase nanoparticles.

[0025] 2. The preparation conditions of the present invention are mild and controllable, with high repeatability, and a multi-phase heterogeneous composite solid oxide fuel cell anode material can be obtained, which has broad application prospects in the field of high-performance electrode preparation for fuel cells.

[0026] 3. The present invention uses a sol-gel method to self-assemble and form an anode material precursor having a composite of perovskite oxide and fluorite oxide. The raw materials are cheap, the preparation process is simple, the cycle is short, and it is suitable for large-scale mass production.

[0027] 4. The present invention prepares anode materials with uniformly dispersed alloy / metal oxide nanoparticles through an in-situ reconstruction method, which significantly improves the specific surface area and active site density of the anode material, optimizes the ion / electron conduction path, promotes the transmission and diffusion of fuel gas and its adsorption and desorption and electrochemical reaction on the electrode surface, thereby enhancing the catalytic activity of the anode material of the present invention. The preparation process is simple and efficient, with good controllability and high repeatability.

[0028] 5. Compared with the traditional solid-phase mixing method, the size of the alloy particles on the surface of the anode material of the present invention is only 10 to 15 nm, and the particle size distribution is more uniform. The operation is simple and easy, and the required equipment is simple and easy to operate.

[0029] 6. The solid oxide fuel cell anode material using the anode material of the present invention has excellent catalytic methanol electrochemical oxidation reaction ability, effectively solving the problems of the existing solid oxide fuel cell in the medium temperature range of 600-700°C and insufficient catalytic activity and anti-carbon deposition ability in the methanol fuel atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a scanning electron microscope photograph of the anode material of Example 1.

[0031] Figure 2 It is the X-ray diffraction pattern of Example 1 (60wt% L9CN7CF-40wt% SDC) and Comparative Example (sm-60wt% L9CN7CF-40wt% SDC).

[0032] Figure 3 It is the X-ray diffraction pattern after reduction of Example 1, Examples 7, 8 and the comparative example.

[0033] Figure 4 It is a transmission electron microscope photograph of the anode material of Example 1 and a surface scan of each element.

[0034] Figure 5 It is a thermogravimetric analysis curve diagram of the anode materials after carbon deposition in Example 1, Examples 7, 8 and the comparative example.

[0035] Figure 6 It is a power density curve of the solid oxide fuel cell anode symmetric cell made of the anode materials of Example 1, Examples 7, 8 and the comparative example at 700°C using methanol as fuel.

[0036] Figure 7 It is a power density curve of a single cell supported by the anode material of Example 1 using methanol as fuel at 550-700°C.

[0037] Figure 8 It is a comparison diagram of polarization impedance of solid oxide fuel cell anode symmetric cells made of anode materials of Example 1, Examples 7, 8 and Comparative Example in a methanol atmosphere at 700°C. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] (1) According to the chemical formula 60wt%La 0.9 Ce 0.1 Ni 0.7 Co 0.15 Fe 0.15 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9 The stoichiometric ratio of (60wt% L9CN7CF-40wt% SDC) and the molar ratio corresponding to the number of elements were used to weigh the raw materials La(NO3)3·6H2O, Ce(NO3)3·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Fe(NO3)3·9H2O required for metal ion solution A, and the raw materials Sm(NO3)3·6H2O and Ce(NO3)3·6H2O required for metal ion solution B;

[0041] (2) dissolving the raw materials required for the metal ion solution A and the metal ion solution B in deionized water respectively to obtain a mixed solution A and a mixed solution B;

[0042] (3) Weighing the required mass of ethylenediaminetetraacetic acid according to the molar ratio of ethylenediaminetetraacetic acid to metal ions in metal ion solution A and metal ion solution B of 1:1, adding an appropriate amount of ammonia water at 65° C. to completely dissolve the ethylenediaminetetraacetic acid to form ammonia water containing ethylenediaminetetraacetic acid, and adding ammonia water containing ethylenediaminetetraacetic acid of corresponding concentrations to mixed solution A and mixed solution B, respectively, to obtain metal ion solution A and metal ion solution B;

[0043] (4) adding water to metal ion solution A and metal ion solution B until the total metal ion concentration is 0.33 mol / L, and stirring continuously;

[0044] (5) weighing anhydrous citric acid and adding it to metal ion solution A and metal ion solution B respectively according to a molar ratio of anhydrous citric acid to metal ions in metal ion solution A and metal ion solution B of 1.5:1;

[0045] (6) adjusting the pH value of each metal ion solution to 6.0-7.0 with concentrated ammonia water, raising the solution temperature to 80-90° C., and gradually forming sol A and sol B from metal ion solution A and metal ion solution B under continuous stirring and evaporation;

[0046] (7) After the two sols are uniformly mixed in a mass ratio of 6:4, the mixture is continuously stirred at 80 to 90° C. to form a precursor gel; the obtained precursor gel is dried at 100 to 120° C. for 12 to 18 hours, and then calcined at 750 to 800° C. for 5 hours to obtain a precursor;

[0047] (8) reducing the obtained precursor in a 5% H2+95% Ar mixed gas atmosphere at a gas flow rate of 70 to 90 mL / min and maintaining the temperature at 650 to 750°C for 2 to 3 hours to obtain an anode material;

[0048] Embodiment 2:

[0049] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La 0.9 Ce 0.1 Ni 0.8 Co 0.1 Fe 0.1 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9

[0050] (60wt%L9CN8CF-40wt%SDC).

[0051] Embodiment 3:

[0052] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La0.8 Ce 0.2 Ni 0.8 Co 0.1 Fe 0.1 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9

[0053] (60wt%L8CN8CF-40wt%SDC).

[0054] Embodiment 4:

[0055] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La 0.8 Ce 0.2 Ni 0.7 Co 0.15 Fe 0.15 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9

[0056] (60wt%L8CN7CF-40wt%SDC).

[0057] Embodiment 5:

[0058] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La 0.7 Ce 0.3 Ni 0.8 Co 0.1 Fe 0.1 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9

[0059] (60wt%L7CN8CF-40wt%SDC).

[0060] Embodiment 6:

[0061] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La 0.7 Ce 0.3 Ni 0.7 Co 0.15 Fe 0.15 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9

[0062] (60wt%L7CN7CF-40wt%SDC).

[0063] Embodiment 7:

[0064] The difference from Example 1 is that the chemical formula in step (1) is 60wt% LaNi 0.7 Co 0.15 Fe 0.15 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9 (60wt% L10CN7CF-40wt% SDC). Metal ion solution A does not contain Ce(NO3)3·6H2O.

[0065] Embodiment 8:

[0066] The difference from Example 1 is that the chemical formula in step (1) is 60wt%La 0.9 Ce 0.1 NiO 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9 (60wt% L9CN-40wt% SDC). Metal ion solution A does not contain Co(NO3)2·6H2O and Fe(NO3)3·9H2O.

[0067] Comparative Example:

[0068] (1) According to the chemical formula sm-60wt%La 0.9 Ce 0.1 Ni 0.7 Co 0.15 Fe 0.15 O 3-δ -40wt%Sm 0.2 Ce 0.8 O 1.9 The stoichiometric ratio of (sm-60wt% L9CN7CF-40wt% SDC) and the molar ratio corresponding to the number of elements are used to weigh La(NO3)3·6H2O, Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Fe(NO3)3·9H2O raw materials, that is, the molar ratio of the above raw materials is 0.9:0.1:0.7:0.15:0.15, add them into a ball mill, use ethanol as a dispersant, and ball mill for 12 hours; after drying at 100°C for 12 hours, a product precursor is obtained, which is transferred to a muffle furnace and calcined at 750-800°C in an air atmosphere for 2 hours to obtain L9CN7CF powder;

[0069] (2) According to the stoichiometric ratio of the above chemical formula and the molar ratio corresponding to the number of elements, weigh the Sm(NO3)3·6H2O and Ce(NO3)3·6H2O raw materials; dissolve all the weighed powders in deionized water to form a transparent and clear solution with a total metal ion concentration of 0.15 mol / L; add urea to the solution in an amount to form a urea concentration of 1 mol / L and ultrasonically dissolve it. The solution is placed in a hydrothermal kettle and reacted at 140°C for 5 hours to obtain a precipitate. The precipitate is washed with distilled water several times and then washed twice with anhydrous ethanol. The washed precipitate is dried at 100°C for 12 hours to obtain a product precursor, which is transferred to a muffle furnace and calcined at 700°C in an air atmosphere for 2 hours to obtain SDC powder;

[0070] (3) After the two powders were uniformly mixed in a mass ratio of 6:4, the ball milling was continued for 12 hours; after drying at 100° C. for 12 hours, a product precursor was obtained, which was transferred to a muffle furnace and calcined in an air atmosphere at 750-800° C. for 2 hours to obtain a precursor powder;

[0071] (4) The precursor obtained in step (3) was reduced in a mixed atmosphere of 5% H2 + 95% Ar with a gas flow rate of 70-90 mL min -1 , and then maintained at 650-750°C for 2-3h for reduction to obtain the anode material.

[0072] Example sample test:

[0073] SDC-(Li 0.67 Na 0.33 )2CO3 as electrolyte, LiNiO2-SDC-(Li 0.67 Na 0.33 )2CO3 is used as the cathode, and the anode materials of each embodiment and comparative example are combined to prepare an electrolyte-supported solid oxide fuel cell by screen printing. Hydrogen is passed through the anode side, and pre-reduction is performed for 2 hours. Afterwards, methanol is passed through the anode side and oxygen is passed through the cathode side, and the electrochemical performance of a single cell is tested at 700°C. The electrochemical performance of the anode material of Example 1 is tested at 550°C, 600°C and 650°C at the same time. As shown in Figures 6 to 8, the electrochemical performance of Example 1 prepared by the method of the present invention is significantly better than that of the comparative example prepared by ball milling.

[0074] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a solid oxide fuel cell anode material, characterized in that: Self-assembled (La 1-x Ce x )(Ni 1-2y Co y Fe y ) 3-δ -Ce 0.8 Sm 0.2 O 1.9 is a precursor, which is reduced and reconstructed in situ, wherein the value range of x is 0≤x≤0.3, the value range of y is 0≤y≤0.2, δ is the oxygen vacancy content, 0≤δ≤0.15; the (La 1-x Ce x )(Ni 1- 2y Co y Fe y ) 3-δ The mass percentage is 50-70%, Ce 0.8 Sm 0.2 O 1.9 The mass percentage is 30-50%; specifically, the method comprises the following steps: (1) nitrates of lanthanum, cerium, nickel, cobalt and iron are mixed and dissolved in water, and then ammonia water in which ethylenediaminetetraacetic acid is dissolved is added and mixed uniformly to obtain a metal ion solution A; (2) samarium and cerium nitrates are mixed and dissolved in water, and then ammonia water in which ethylenediaminetetraacetic acid is dissolved is added and mixed evenly to obtain a metal ion solution B; (3) adding citric acid to metal ion solution A and metal ion solution B respectively, adjusting the pH of the solution with aqueous ammonia, and stirring the mixture at 80-90° C. to obtain sol A and sol B respectively; (4) mixing sol A and sol B and continuing to stir to obtain a precursor gel; (5) drying the precursor gel at 100-120° C. for 12-18 h, and then calcining at 750-800° C. for 5-10 h to obtain a precursor; (6) The obtained precursor is reduced in a mixed gas atmosphere of hydrogen and argon at a hydrogen flow rate of 70 to 90 mL / min to obtain an anode material.

2. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: The lanthanum, cerium, nickel, cobalt, iron and samarium ions are prepared by using the molar ratio of the elements indicated by the chemical formula of the precursor.

3. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: The anode material is a structure in which active metal and metal oxide multiphase nanoparticles are evenly distributed; when y is not equal to 0, the active metal nanoparticles are NiCoFe alloy.

4. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: The molar ratio of ethylenediaminetetraacetic acid to metal ions in metal ion solution A and metal ion solution B in step (1) and step (2) is 1:1; the total concentration of metal ions in metal ion solution A and metal ion solution B in step (1) and step (2) is 0.15-0.33 mol / L.

5. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: Step (3) adjusts the pH value of the solution to 6-7; in step (3), the molar ratio of citric acid to the metal ions in the metal ion solution A and the metal ion solution B is 1:(1.5-2).

6. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: The stirring time in step (4) is 4 to 6 hours.

7. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: After calcination in step (5), the slurry is sieved through a 200-300 mesh sieve.

8. The method for preparing anode material of solid oxide fuel cell according to claim 1, characterized in that: The volume of hydrogen in step (6) accounts for 5-10% of the mixed gas; the reduction temperature is 650-750° C. and the time is 2-3 hours.

9. Use of a solid oxide fuel cell anode material prepared by the method according to any one of claims 1 to 3 in a carbon deposition resistant solid oxide fuel cell.